Reconstruction of maxillary cemento-ossifying fibroma defect with buccal pad of fat - Subramonian Sivaraj; Pratheep Jeevadhas (Wolters Kluwer Medknow Publications, 2013)
A cemento-ossifying fibroma (COF) is a rare benign neoplasm of maxilla when compared with mandible (World Health Organization, 1992). COF of maxilla may be quite large and locally very aggressive lesion. These tumor mass was peeled out by en-bloc excision using gentle blunt dissection. This paper presents 35-year-old male patient who had a gradually expanding lobular mass in the left maxillary posterior region for past 1 year. He has been treated successfully by surgical en-bloc resection. Various techniques were used to reconstruction the defect. Buccal pad of fat is a simple technique having advantages like good vascularity, adaptability, good closure of the defect with favorable prognosis.